Investigation of the longitudinal wind power spectra at the gorge terrain. Issue 11 (November 2017) - Hu, Peng; Li, Yongle; Xu, GJ; Han, Yan; Cai, CS; Xue, Fanrong
This study investigates the fundamental characteristics of the longitudinal wind power spectra at the gorge terrain. First, a simplified V-shaped gorge terrain model, representing usual deep-cutting gorge terrains where long-span bridges usually straddle, was introduced for the wind tunnel test. The longitudinal wind power spectra at the gorge center were analyzed in detail and compared with those of the simulated oncoming wind. Then, a practical calculation method was proposed to directly calculate the power spectra values at the gorge terrain based on the oncoming wind field and minimum wind parameters at the gorge center. Finally, an infield V-shaped deep-cutting gorge terrain model was also introduced for the wind tunnel test, and the obtained wind power spectra further validated the proposed calculation method. The results show that for both gorge terrain models, the power spectra values in the low-frequency range become closer to those of the oncoming wind with the measurement positions moving away from the ground, while good agreements are always found in the high-frequency range for all of the specified measurement positions. The proposed calculation method can calculate the power spectra values at these two gorge terrains with relatively high accuracy. It is hoped that this study can more conveniently provide informative guidelines for determining the wind power spectra values for similar gorge terrains in engineering practices than traditional wind tunnel tests or computational fluid dynamics numerical simulations.